Evaluasi Kinerja Beton Ramah Lingkungan dengan Penambahan Superplastisizer dan Hydrated Lime - Cahyani, Rizki Amalia Tri; Rusdianto, Yunan; Cahyadi, Ahmad Zainil; Trisyulianto, Parlingga; Darmawan, Azhar Adi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study investigates the performance of environmentally friendly concrete by utilizing superplasticizer and hydrated lime as filler materials. The superplasticizer was used to simultaneously reduce the water and cement content in the concrete mix, while hydrated lime was added as a filler to compensate for the reduced paste volume. The evaluation was conducted through compressive strength testing, water absorption, and sorptivity measurements. The results show that the incorporation of superplasticizer significantly improved both workability and compressive strength, despite a 10% reduction in water and cement content. This mixture demonstrated the best performance, indicated by the highest slump and compressive strength values. Conversely, the addition of hydrated lime resulted in a 2.7% decrease in compressive strength compared to the control mix. Water absorption and sorptivity tests revealed that concrete containing hydrated lime had lower total water absorption capacity but exhibited a higher initial rate of water absorption. These findings suggest the need for more diverse testing methods or an expanded set of research variables to obtain a more comprehensive assessment of concrete's resistance to water penetration.